Herpetofauna of Two Habitats in Northeast Pulau Langkawi, Kedah, Peninsular Malaysia - B, Daicus,; R, Hashim; Ramli, Rosli; Sofian-Azirun, M. (Malaysian Journal of Science, 2005)
Ten species of amphibians, four species of lizards and one species of snake were recorded from two habitats of northeast Pulau Langkawi, Kedah. These were amphibians - Bufo asper, B. melanostictus, Fejervarya limnocharis, Limnonectes blythi, L. malesianus, Microhyla berdmorei, Polypedates leucomystax, Rana chalconota, R. erythraea, R. hosii; lizards - Draco melanopogon, D. volan, Gekko gecko, Mabuya multifasciata; and snake - Chrysopelea paradisi.